2020
DOI: 10.5114/aoms.2020.95462
|View full text |Cite
|
Sign up to set email alerts
|

Association between myeloperoxidase rs2333227 polymorphism and susceptibility to coronary heart disease

Abstract: Coronary heart disease (CHD) accounts for the most morbidity and mortality all over the world [1]. Heritable factors account for 30-60% of the susceptibility to coronary heart disease, and therefore genotypic variants are potential modifiers of predisposition to coronary heart disease. Our previous study demonstrated that apolipoprotein A1 polymorphism was associated with coronary artery disease [2]. Recently, researchers have revealed myeloperoxidase (MPO) as a new potential mutation associated with the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…When the body is stimulated by external stimulation, the imbalance of OS result in the formation of signi cant amounts of lipid products and oxides in the arterial walls, which induces an immune response and an in ammatory reaction(Abraham and Marchuk 2014). Several studies have shown that MPO mediates the formation of OS and in ammatory reactions and is a signi cant in ammatory marker(Love et al 2017;Zhang et al 2020). Moreover, the oxidative modi cation of MPO causes the formation of arterial plaques, and the level of MPO is closely associated with CHD(Gorudko et al 2012).…”
mentioning
confidence: 99%
“…When the body is stimulated by external stimulation, the imbalance of OS result in the formation of signi cant amounts of lipid products and oxides in the arterial walls, which induces an immune response and an in ammatory reaction(Abraham and Marchuk 2014). Several studies have shown that MPO mediates the formation of OS and in ammatory reactions and is a signi cant in ammatory marker(Love et al 2017;Zhang et al 2020). Moreover, the oxidative modi cation of MPO causes the formation of arterial plaques, and the level of MPO is closely associated with CHD(Gorudko et al 2012).…”
mentioning
confidence: 99%